STUDI ANALISIS DAYA DUKUNG TANAH TERHADAP FONDASI DALAM BERDASARKAN DATA SPT PADA BANGUNAN PELIMPAH DARI BENDUNGAN TUGU - Muhammad Iqbal Hamidi; Imam Achmad Sadisun (KURVATEK, 2021)
The massive infrastructure works in Indonesia currently requires good planning and implementation. The research location is included in the spillway construction project of the Tugu Dam. The bearing capacity research is limited by calculated for the deep foundation in the boredpile type with a diameter of 0.8 meters used SPT (Standard Penetration Test) data. SPT testing is carried out based on SNI 4153:2008. Calculated of ultimate end bearing capacity (Qp) on volcanic breccia and andesite has a value of 19.60 Tons. Meanwhile, the value of ultimate frictional resistance (Qs) in this volcanic breccia and andesite has a value of 0.84 Ton, this ultimate frictional resistance value increases according to the planned depth of the foundation and is adjusted to the building loaded. The altered sandy silt layer, the ultimate end resistance (Qp), and the friction blanket resistance (Qs) varies according to the average value of N-SPT. The difference in the value of N-SPT in the same soil layer is due to geological processes such as hydrothermal alteration and rock weathering.